Analysis of Knowledge of The Use of Personal Protective Equipment (PPE) Against Working Diseases in Workers at CV. Bintang Indah Marmer Campurdarat, Tulungagung District - Gusandan Maulada Al Farobby; Amarin Yudhana (Universitas STRADA Indonesia, 2021)
Work-related illnesses which are risks that must be faced by workers in carrying out work, including accidents that occur on the way from home to work, and returning home via normal or reasonable roads.. The purpose of this study is to analyze the influenceknowledge of the use of Personal Protective Equipment (PPE) against the incidence of occupational diseases in workers at CV. Bintang Indah Marmer Campurdarat, Tulungagung Regency.The research design was an observational quantitative study with a cross sectional approach with the focus of the research being aimed at analyzing the influence of knowledge on the use of Personal Protective Equipment (PPE) on the incidence of occupational diseases in workers at CV. Bintang Indah Marmer Campurdarat, Tulungagung Regency.with a population of 46 respondents and a sample of 41 respondents who were drawn using the simple random sampling technique. The findings show that hNearly half of the respondents have knowledge of the use of PPE in the moderate category as many as 17 respondents (41.5%). Most of the respondents had experienced respiratory problems as many as 21 respondents (51.2%).The results of the study used the test Logistic Regression It shows that the p-value is 0.002 <0.05, then H0 is rejected and H1 is accepted, so it is concluded that there is the influence of knowledge on the use of Personal Protective Equipment (PPE) on the incidence of occupational respiratory disorders in workers at CV. Bintang Indah Marmer Campurdarat, Tulungagung Regency. It is expected that respondents when doing work that has a high risk of accidents while working to use personal protective equipment (PPE) completely and behave in a safe work so that work security and safety can be increased.